In Situ Detection and Quantification of AR-V7, AR-FL, PSA, and KRAS Point Mutations in Circulating Tumor Cells. (1st March 2018) - El-Heliebi, Amin; Hille, Claudia; Laxman, Navya; Svedlund, Jessica; Haudum, Christoph; Ercan, Erkan; Kroneis, Thomas; Chen, Shukun; Smolle, Maria; Rossmann, Christopher; Krzywkowski, Tomasz; Ahlford, Annika; et al.
Abstract: BACKGROUND: Liquid biopsies can be used in castration-resistant prostate cancer (CRPC) to detect androgen receptor splice variant 7 (AR-V7), a splicing product of the androgen receptor. Patients with AR-V7-positive circulating tumor cells (CTCs) have greater benefit of taxane chemotherapy compared with novel hormonal therapies, indicating a treatment-selection biomarker. Likewise, in those with pancreatic cancer (PaCa), KRAS mutations act as prognostic biomarkers. Thus, there is an urgent need for technology investigating the expression and mutation status of CTCs. Here, we report an approach that adds AR-V7 or KRAS status to CTC enumeration, compatible with multiple CTC-isolation platforms. METHODS: We studied 3 independent CTC-isolation devices (CellCollector, Parsortix, CellSearch) for the evaluation of AR-V7 or KRAS status of CTCs with in situ padlock probe technology. Padlock probes allow highly specific detection and visualization of transcripts on a cellular level. We applied padlock probes for detecting AR-V7, androgen receptor full length (AR-FL), and prostate-specific antigen (PSA) in CRPC and KRAS wild-type (wt) and mutant (mut) transcripts in PaCa in CTCs from 46 patients. RESULTS: In situ analysis showed that 71% (22 of 31) of CRPC patients had detectable AR-V7 expression ranging from low to high expression [1–76 rolling circle products (RCPs)/CTC]. In PaCa patients, 40% (6 of 15) had KRAS mut expressing CTCs with 1 to 8 RCPs/CTC. In situ padlock probe analysis revealed CTCs with no detectable cytokeratin expression but positivity for AR-V7 or KRAS mut transcripts. CONCLUSIONS: Padlock probe technology enables quantification of AR-V7, AR-FL, PSA, and KRAS mut/wt transcripts in CTCs. The technology is easily applicable in routine laboratories and compatible with multiple CTC-isolation devices.